Rancangan pengukuran kinerja layanan publik: Studi kasus pelayanan pengujian alat ventilator BPFK Kemenkes RI - Sugiri Widjajanto; Yulio Agefa Purmala; Dina Rosdiana (Universitas Mercu Buana, 2020)
Various organizations in Indonesia collaborate to make various types of medical ventilator prototypes due to Covid-19 demand. PERMENKES RI no. 54/2015 obliged all medical devices must go through testing and inspection process by authorized institution Badan Pengamanan Fasilitas Kesehatan (BPFK) under the Ministry of Health of Republik Indonesia. This article has designed a performance measurement for the ventilator testing laboratory using MBNQA (Malcolm Baldrige National Quality Award) approaching which is integrated with ISO/SNI-17025 requirement of both management and technical. There are ten technical requirements and fifteen management requirements of ISO/SNI-17025 inserted into seven Baldrige criteria: leadership, strategic planning, customer focus, management of assessment, analysis & knowledge, personnel, operations and results. Data and information is designed to be collected through interview and questionnaire on a Likert scale. The response score for each question and feedback will be evaluated based on the process and outcome dimensions. Further research is required to validate the questionnaire, conduct interviews, segregate management and laboratory technician questions, and add evaluation of ADLI (approach, dissemination, learning & integration) and LeTCI (levels, trends, comparisons & integration) methods as well the ADLI & LeTCI score and matrix results. The obtained MBNQA score will indicate award category of the laboratory as world leader or benchmark leader or only at early development stage.